D. T. Suzuki: post-orientalistisk zen-tænker - Borup, Jørn (Religionsvidenskabeligt Tidsskrift, 2018)
ENGLISH ABSTRACT: Japanese D. T. Suzuki occupies a unique position in the history of Zen Buddhism's migration from East to West. His many publications on Zen until a few decades ago were the only channel to knowledge about this universe, and 'Suzuki Zen' in itself has been a catalyst for lived Zen Buddhism in the West. This article describes Suzuki's life and places his understanding of Zen, Buddhism and religion in a historical and network-theoretical framework. It is concluded that the relevant critique of Suzuki ought to be counterbalanced, so that his achievements are also acknowledged 50 years after his death. DANSK RESUME: Japanske D. T. Suzuki indtager en unik position inden for zen-buddhismens vandring fra øst til vest. Hans mange udgivelser om zen har indtil for få årtier siden været eneste kanal til viden om dette univers, og 'Suzuki-zen' har i sig selv været katalysator for levende zen-buddhisme i Vesten. Artiklen beskriver Suzukis liv og sætter hans forståelse af zen, buddhisme og religion i en historisk og netværksteoretisk ramme. Det konkluderes, at den helt relevante kritik af Suzuki bør afbalanceres, så de faglige fortjenester faktisk også påskønnes 50 år efter hans død.